Validation and revision of the questionnaire to explore human factors and their technical potential for lower limb prosthetics. Issue 1 (3rd February 2021) - Herbst, Jonathan; Polanski-Schräder, Lucas MT; Vogt, Joachim; Schürmann, Tim; Beckerle, Philipp
Abstract : Background: A variety of instruments exist to measure human factors for lower limb amputation and prosthesis research. Yet, there is no valid or reliable tool available that focuses on technical potentials. Objective: This study aimed to validate and revise the Questionnaire to Explore Human Factors and their Technical Potential. Study Design: Cross-sectional study Methods: A total of 150 persons with lower limb amputation from Germany participated in the study. Statistical properties, including Cronbach's alpha, item difficulty, item-total correlation, and distribution of missing values were calculated. Thresholds for acceptable psychometric properties were defined, unsuitable items were removed, and problematic items were reviewed regarding formulation. Results: The Cronbach's alpha for subscales within the Questionnaire to Explore Human Factors and their Technical Potential were between 0.72 and 0.89. A total of 56 items showed acceptability, and 14 items had problematic item property values. Four of those items were reformulated, five were excluded, six were left in the scale, and an additional one was added to the scale. Conclusion: Evaluation of the Questionnaire to Explore Human Factors and their Technical Potential indicates it exhibits good internal consistency and acceptable psychometric properties. The scale was revised and is recommended to explore aspects of technical prosthesis development. Clinical relevance: Our results show that the revised Questionnaire to Explore Human Factors and their Technical Potential may serve as a reliable and valid means, when designing prostheses, both during development and clinical evaluations and fittings, to assess the technical potential of lower limb prostheses directly according to the needs of users with lower-limb amputations.